Pengaruh Karakteristik Usia dan Gender Santri di Ma’had Bakkah Martapura terhadap Kesadaran Pemilahan Sampah Organik dan Anorganik - Hesti Wijayanti; Primata Mardina; Rinna Juwita; Lailan Ni'mah; Jefriadi Jefriadi; Desi Nurandini; Indah Retno Wulandary; Yulia Nurul Ma'rifah (Universitas Lambung Mangkurat, 2026)
Children's awareness of disposing of waste in designated bins is a crucial factor in environmental health education, fostering a clean and healthy environment. A lack of understanding among children regarding waste management can be addressed through educational approaches that provide knowledge about organic and inorganic waste types. These efforts should begin early, during the formative